(untitled) ("Journal "U". Economy. Management. Finance.", 2026)
The article examines flexible forms of employment and their role in maintaining macroeconomic stability during economic crises. The paper considers three key forms of employment: part-time employment, remote work, outsourcing (outstaffing). Conclusions are drawn about the function and role of flexible forms of employment in the labor market.